Challenges faced by teachers in the pandemic and post-pandemic scenario: teachers and the challenges encountered in time of a pandemic - Santos, Dayane Rodrigues dos (2021)
This article has as its general theme the challenges faced by teachers in times of pandemic. The obstacles that the population encountered as a result of the new Coronavirus pandemic affected various sectors of society, especially education, more than two thirds of students in the world suffered damage to their teaching-learning process, with high levels of inequalities in this sector, lack of access and support for students and especially teachers was unprecedented. Faced with the problem, the objective was to analyze what are the challenges faced by teachers in times of pandemic? This work is a theoretically based research based on articles, online journals and theses. So that with these recent research data, this work becomes relevant in discussing and understanding in general these new challenges in basic education in times of pandemic.